Comparative Assessment of the Fenestration, Dehiscence Frequency and Facial Bone Thickness in the Maxillary Anterior Region of Smokers Versus Non-Smokers: A Cross-Sectional Study - Ferena sayar; Amirhossein Farahmand; Bahar Ebrahimi kordasiabi; Ladan Hafezi; Mahsa soleimani (International Journal of Dentistry)
Conclusion: The study found that smoking reduced the thickness of the labial bone in the anterior maxillary regions. In addition, female smokers had a higher frequency of fenestrations in the right premolar and left canine regions, and on average, smoking patients had the highest rate of dehiscence in the left premolar–maxillary region.